Fetal Heart Rate Tracings and Adverse Outcomes Among Term Small versus Appropriate for Gestational Age - Patel, Shareen; Cagino, Kristen A; Roberts, Aaron W; Wiley, Rachel; Cortes, Christina; Zullo, Fabrizio; Mendez-Figueroa, Hector; Chauhan, Suneet P (American Journal of Perinatology)
Objective To compare the patterns of fetal heart rate tracings (FHRT), and outcomes among individuals with small (birthweight [BW] < 10% for gestational age [GA]; SGA) versus appropriate (BW at 10-89% for GA; AGA) newborns at term (≥37.0 weeks). Study Design Our retrospective cohort study included consecutive deliveries over 15 months at a Level IV center. FHRTs were reviewed by obstetricians blinded to maternal and neonatal outcomes. The inclusion criteria were non-anomalous singletons, cataloged as SGA or AGA birthweight using Alexander et al. nomogram. In 20-minute segments, the last 120 minutes of tracing were characterized. Rates of cesarean delivery (CD) and composite neonatal adverse outcomes (CNAO) were compared. Results Of 5,160 deliveries, 3,029 (58.7%) met the inclusion criteria, and among them, 422 (13.9%) were SGA and 2,607 (86.1%) AGA. There were no differences in FHRT baseline, variability, or accelerations. Compared to AGA, SGA was more likely to have prolonged decelerations (11.8% vs. 8.4%, p=0.021), recurrent decelerations with  50% of contractions (21.3% vs. 16.5%, p=0.014). Overall the presence of category II FHRT or not was similar between the SGA (91.2%) and AGA (88.5%; P=0.097). Persistent category II FHRT was significantly more common among SGA (37.4%) than AGA (28.1%; a OR 1.47; 95% CI 1.47-1.82) newborns. The rate of CD for non-reassuring FHRT was similar among the two groups. CNAO occurred in 1.4% in both SGA and AGA neonates (p=0.95). Conclusion In our cohort of those with fetal monitoring prior to delivery at ≥37 weeks: persistent category II FHRT at the end of labor was significantly more common in SGA compared to AGA neonates, however composite neonatal morbidity did not differ between the two groups. Our analysis provides data for shared decision making that among SGA newborns, abnormalities of FHRT are not linked with adverse outcomes.